2010
DOI: 10.1021/es9029717
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Microbial Carbon Sources and Cycling during Remediation of Petroleum Hydrocarbon Impacted Soil Using Natural Abundance 14C Analysis of PLFA

Abstract: In a petroleum impacted land-farm soil in Sarnia, Ontario, compound-specific natural abundance radiocarbon analysis identified biodegradation by the soil microbial community as a major pathway for hydrocarbon removal in a novel remediation system. During remediation of contaminated soils by a plant growth promoting rhizobacteria enhanced phytoremediation system (PEPS), the measured Delta(14)C of phospholipid fatty acid (PLFA) biomarkers ranged from -793 per thousand to -897 per thousand, directly demonstrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 50 publications
(110 reference statements)
3
21
0
Order By: Relevance
“…Compound-specific radiocarbon analysis of cellular biomass can be compared with the radiocarbon content of different OC sources that have a unique radiocarbon signature to provide a direct measure of carbon substrate utilization in the environment (15)(16)(17)(18)(19)(20)(21). For example, this method has been used to document the preference of microbes for degradation of petroleum hydrocarbons and utilization of organic matter derived from shale weathering.…”
mentioning
confidence: 99%
“…Compound-specific radiocarbon analysis of cellular biomass can be compared with the radiocarbon content of different OC sources that have a unique radiocarbon signature to provide a direct measure of carbon substrate utilization in the environment (15)(16)(17)(18)(19)(20)(21). For example, this method has been used to document the preference of microbes for degradation of petroleum hydrocarbons and utilization of organic matter derived from shale weathering.…”
mentioning
confidence: 99%
“…Further experiments definitively showed that the PHC were degraded in situ in the rhizosphere and that biodegradation by the microbial community in PHC-impacted soils is a major pathway for PHC removal by PEPS [128,136]. Further experiments definitively showed that the PHC were degraded in situ in the rhizosphere and that biodegradation by the microbial community in PHC-impacted soils is a major pathway for PHC removal by PEPS [128,136].…”
Section: Development Proof and Full-scale Application Of Pepsmentioning
confidence: 93%
“…This provides multiple benefits: it eliminates ecological risk; and PGPR isolated from specific PHC-contaminated soils are PHC tolerant and are often PHC degraders, using PHC as their source of carbon in the nutrient-poor soils [136]. This strategy also facilitates native habitat reconstruction/reclamation following remediation.…”
Section: Pgpr-enhanced Phytoremediation System(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…CBM) into biomass and organic carbon pools. Carbon-14 values are readily corrected for kinetic isotope fractionation effects by a d 13 C value-based normalization (Stuiver & Polach, 1977) and have been successfully used to trace the incorporation of fossil carbon by microorganisms in a variety of environments (Petsch et al, 2001;Pearson et al, 2005;Slater et al, 2005Slater et al, , 2006Wakeham et al, 2006;Ahad et al, 2010;Cowie et al, 2010;. We used a dual carbon isotope approach, in combination with compound-specific biomarker and 16s rDNA techniques, to characterize methanotroph and nonmethanotroph populations in soil overlying a natural coal-bed methane (CBM) seep.…”
Section: Introductionmentioning
confidence: 99%